2008
DOI: 10.1111/j.1365-2435.2008.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Browsed Betula pubescens trees are not carbon‐limited

Abstract: Summary 1.Slower growth after repetitive browsing of young trees has been attributed to a carbon (C) limitation, but data from long-term studies are lacking. To determine if repeated summer browsing causes a C (source) limitation in trees in the long-term, we analysed the non-structural carbohydrate (NSC) and nitrogen (N) concentrations and pools of Betula pubescens saplings subjected to different clipping treatments (unclipped, 33% and 66% shoot removal) for 7 years. 2. The short-term effect of browsing on C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 53 publications
6
64
2
Order By: Relevance
“…The seedlings may thereafter grow vigorously once deer herbivory stops. Indeed, it was shown that Betula species may tolerate severe clipping over prolonged periods (Kinnaird 1974, Palacio et al 2008. Although regeneration in the delayed exclosures was a mix between browse-sensitive and resistant species, we expect the climax to be dominated by the only abundant late-successional species: Picea spp.…”
Section: Discussionmentioning
confidence: 93%
“…The seedlings may thereafter grow vigorously once deer herbivory stops. Indeed, it was shown that Betula species may tolerate severe clipping over prolonged periods (Kinnaird 1974, Palacio et al 2008. Although regeneration in the delayed exclosures was a mix between browse-sensitive and resistant species, we expect the climax to be dominated by the only abundant late-successional species: Picea spp.…”
Section: Discussionmentioning
confidence: 93%
“…Non-structural carbohydrates (NSC) are major forms of C reserves and they are used for evaluating the C balance (Chapin et al, 1990;Palacio et al, 2008;Sala et al, 2010). Whenever photosynthetic production is insufficient to meet the metabolic demands (i.e., C gain does not meet C demand), the amount of NSC must decrease as trees mobilize carbohydrates from storage sites (Chapin et al,1990).…”
Section: Non-structural Carbohydrates Of the Two Species Under N And mentioning
confidence: 99%
“…Warmer spring temperatures generally prompt an earlier onset of gross primary production (GPP), but temperature effects on the termination of GPP are less clear. If the temporal relationship between NPP and GPP is altered as temperatures rise, then shifts in C source-sink relationships may, in turn, affect tissue NSC concentrations, an outcome that could have broad ecological consequences for the resilience of forest growth following disturbance or climatic stress [3,[24][25][26][27][28][29][30][31]. Forecasts of future plant tissue NSC have focused on the effects of rising atmospheric CO 2 [32].…”
Section: Introductionmentioning
confidence: 99%